(The Effect of Solvent and Particle Size on The Yield and Piperin Content of Oleoresin from White Pepper Waste (Piper Nigrum Linn) - Gasik Darma; Lucyana -; H.G. Pohan (Balai Besar Industri Agro, 1991)
The study is aimed at increasing the added value of white pepper waste products by producing oleoresin. The solvents used were ethanol 95%, ethyl acetate and dichloro ethane. The particle size of white pepper powder are 40,60,80 and 100 mesh. The highest yield of oleoresin was obtained from 80mesh powder i.e. 14.60% using ethanol 95% ; 14.21% using ethyl acetate and 14.18% using dichloro ethane. The piperine content was 41.39% in ethanol 95%: 37.95% in ethyl acetate and 41.02% in dichloro ethane.